Determinants of Indonesia’s Coffee Export Value: Production, International Prices, and Exchange Rate - Bima Hardi; Mimi Arimbi; Muhammad Safrizal (Cendekia Niaga, 2026)
This study examines the determinants of Indonesia’s coffee export value by assessing the effects of coffee production, international coffee prices, and the rupiah/US dollar exchange rate. Using monthly secondary data from 2021 to 2025 obtained from Statistics Indonesia, Bank Indonesia, and the International Coffee Organization, this study applies an Error Correction Model (ECM) to distinguish short-run dynamics from long-run equilibrium relationships. The results show that, in the long run, international coffee prices and the rupiah/US dollar exchange rate have positive and significant effects on Indonesia’s coffee export value, while coffee production shows a positive but statistically insignificant effect at the 5 percent level. In the short run, exchange rate movements have a significant negative effect, whereas changes in production and international coffee prices are not significant. The negative and significant error correction term confirms the existence of a valid adjustment mechanism toward long-run equilibrium. These findings indicate that Indonesia’s coffee export performance is shaped not only by production capacity but also by global price incentives, exchange rate movements, and market adjustment processes. Policy efforts should therefore prioritize product quality, certification, downstream processing, market diversification, logistics efficiency, and exchange rate stability to strengthen the competitiveness and sustainability of Indonesian coffee exports.